Perancangan Interior Beauty Lounge Salon di Bali - Putu Khatalia Prabasari; Sriti Mayang Sari; Celine Junica Pradjonggo (Intra, 2018)
Salon is a place that is needed by the whole society, ranging from children, teenagers, to adults. Salon is used to perform body treatments and beautification that will make someone appear more confident. In this case, salon visitors can treat and beautify their body from head to toe with various treatments offered by each salon.In general, salon provides various facilities, such as hairdressing, makeup, facial, embroidery eyebrows, manicure pedicure, and others. However, it is rare to find a salon that can provide all the treatments and facilities completely in one place. Sometimes some salons provide only a few treatments because of the limited space owned by the salon. This will affect the consumer's interest to visit the salon because the provided care is incomplete and they will look for other salons to meet their care.Beauty Lounge Salon interior design aims to provide a place that has complete body care and supporting facilities so that customers can use their time efficiently to treat their body. The New Born Beauty design concept which means